(untitled) (Journal of Partial Differential Equations, 2004)
" We study a free boundary problem of parabolic equations with a positive parameter 03c4 included in the coefficient of the derivative with respect to the time variable t. This problem arises from some reaction-diffusion system. We prove that, if 03c4 is large enough, the solution exists for 0 < t < +221e while, if 03c4 is small enough, the solution exists only in finite time."